GROWTH RESPONSE AND PRODUCTION OF KAILAN PLANT (BRASSICA OLERACEA VAR. ALBOGLABRA) ON PROVISION OF BANANA GEDEBOG POC AND COW STATE FERTILIZER - Berliana, Yunida; Nadhira, Ahmad; Wahyudi, Erfan; R., Wahyuni; Nurhayati, Nurhayati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the response of growth and production of Kailan (Brassica oleracea var. Alboglabra) to Gedebog Banana POC and cow manure with different administrations. The study was carried out, Johor Village, Medan Johor District, North Sumatra from August 2019 to November 2019. The method used in this study was a Factorial Randomized Block Design (RAK) consisting of two factors, namely: POC Gedebog Banana Dose Factor (A1 = 200ml /L; A2 = 300ml/L and A3 = 400ml/L.). Dosage Factor of Cow Manure (K1 = 5 tons/ha; K2 = 10 tons/ha and K3 = 15 tons/ha). Giving POC Gedebog bananas showed significantly different effects on plant height, wet weight per plant and dry weight of kailan plants, but did not show a significantly different effect on the number of plant leaves. The application of cow manure showed no significant effect on all variables. The interaction of Gedebog Banana POC administration with Cow Manure showed a significantly different effect on plant height and dry weight per plant, but showed no significant effect on the number of plant leaves.